2024
DOI: 10.1021/acs.estlett.4c00066
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous OH Radical Production by Brake Wear Particles

Ting Fang,
Sukriti Kapur,
Kasey C. Edwards
et al.

Abstract: Particulate matter (PM) emitted from road traffic causes adverse health effects upon inhalation and respiratory deposition. Non-exhaust emissions will eventually become the dominant source of traffic PM upon transition to electric vehicles; however, non-tailpipe PM is currently unregulated as its health impacts are still unclear. In this study, we generated brake wear particles (BWPs) with non-asbestos organic, ceramic, and semimetallic brake pads using custom dynamometers and measured aqueous-phase formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…The reduction in metal wear per particle mass suggests that the reduction in the total brake wear factor, PM10, and PM2.5 is predominant (negatively correlated with the ratio of Ba mass per pad mass). However, although outside the scope of this study, a comparison of non-steel pads and low-steel pads (ceramic pads) showed that the formation of OH radicals in the aqueous phase increased with increasing Ba concentration in brake wear particles [73]. We suggest that the prevention of direct adhesion with steel fibers by Ba results in a decrease in metal wear per particle mass [18], an increase in organic mass per particle mass, and a predominant formation of OH radicals derived from organic matter.…”
Section: Bariummentioning
confidence: 82%
See 1 more Smart Citation
“…The reduction in metal wear per particle mass suggests that the reduction in the total brake wear factor, PM10, and PM2.5 is predominant (negatively correlated with the ratio of Ba mass per pad mass). However, although outside the scope of this study, a comparison of non-steel pads and low-steel pads (ceramic pads) showed that the formation of OH radicals in the aqueous phase increased with increasing Ba concentration in brake wear particles [73]. We suggest that the prevention of direct adhesion with steel fibers by Ba results in a decrease in metal wear per particle mass [18], an increase in organic mass per particle mass, and a predominant formation of OH radicals derived from organic matter.…”
Section: Bariummentioning
confidence: 82%
“…We suggest that the prevention of direct adhesion with steel fibers by Ba results in a decrease in metal wear per particle mass [18], an increase in organic mass per particle mass, and a predominant formation of OH radicals derived from organic matter. Further investigation is needed to evaluate the reduction of brake wear particles and health effects, as it is suggested that Ba concentration may be negatively correlated with oxidative potential and OH radical formation in the aqueous phase [73], which would be assumed to be in vivo, when evaluating health effects based on oxidative potential.…”
Section: Bariummentioning
confidence: 99%
“…These correlations suggest an influence of road dust on EPFRs in Fairbanks. Iron and titanium oxides are known to stabilize EPFRs. ,,, Ti is also a major component in brake wear particles . Thus, tight correlations of EPFR v with Fe and Ti suggests that nontailpipe emissions may play a role in stabilization of EPFR, if they are internally mixed.…”
Section: Resultsmentioning
confidence: 99%